The effect of animal-assisted intervention on undergraduate students’ perception of momentary stress - Chute, Andrea; Vihos, Jill; Johnston, Sharon; Buro, Karen; Velupillai, Nirudika (Frontiers in Psychology, 2023)
Background: Student mental wellness is a priority in higher education. Animal Assisted Interventions (AAIs') are gaining momentum in universities across North America (Dell et al., 2015). Aims: This study explored the relationships between AAIs', demographic variables, and perceived momentary stress among university students. Methods: Using a descriptive correlational design, students completed a Perceived Momentary Stress questionnaire that included the Stress Numerical Rating Scale-11 (Stress NRS-11) and the Visual Analog Scale (VAS) to measure perceived stress before and after AAIs'. Data were analyzed using R (4.1.2) (R Core Team, Vienna, Austria) to identify relationships between students' perceptions of momentary stress, AAIs' and sociodemographic and demographic variables. Results: First-year students, female students, and students identifying as sexual minorities were found to benefit the most from AAIs'. Conclusion: Results from this study reflect relationships between exposure to animal-assisted interventions and student demographic variables.